Assessing the impact of energy coaching with smart technology interventions to alleviate energy poverty - Joseph Llewellyn; Titus Venverloo; Fabio Duarte; Carlo Ratti; Cecilia Katzeff; Fredrik Johansson; Daniel Pargman (Scientific Reports)
Abstract Energy poverty affects 550,000 homes in the Netherlands yet policy interventions to alleviate this issue are rare. Therefore, we test two energy coaching interventions in Amsterdam: a static information group (n = 67) which received energy efficient products and one energy-use report, and a smart information group (n = 50), which also had a display providing real-time feedback on energy-use. Results across both groups, show a 75% success rate for alleviating energy poverty. On average homes reduced monthly electricity consumption by 62 kWh (33%), gas by 41 m3 (42%), bills by €104 (53%) and percentage of income spent on energy from 10.1% to 5.3%.